2014
DOI: 10.1063/1.4903169
|View full text |Cite
|
Sign up to set email alerts
|

Origin of traps and charge transport mechanism in hafnia

Abstract: In this study, we demonstrated experimentally and theoretically that oxygen vacancies are responsible for the charge transport in HfO$_2$. Basing on the model of phonon-assisted tunneling between traps, and assuming that the electron traps are oxygen vacancies, good quantitative agreement between the experimental and theoretical data of current-voltage characteristics were achieved. The thermal trap energy of 1.25 eV in HfO$_2$ was determined based on the charge transport experiments.Comment: 5 pages, 5 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 36 publications
3
30
0
2
Order By: Relevance
“…1-3 It was shown that charge transport mechanism in HfO 2 and ZrO 2 is phonon-assisted tunneling between traps. 2, 4 The charge transport mechanism of ternary high-j solid solution Hf 0.5 Zr 0.5 O 2 still remains unknown.…”
mentioning
confidence: 99%
“…1-3 It was shown that charge transport mechanism in HfO 2 and ZrO 2 is phonon-assisted tunneling between traps. 2, 4 The charge transport mechanism of ternary high-j solid solution Hf 0.5 Zr 0.5 O 2 still remains unknown.…”
mentioning
confidence: 99%
“…HfO 2 has wide bandgap (5.7 eV) and high dielectric constant (22) and exhibits good thermodynamic stability. However, HfO 2 suffers from important current leakage which has been related to neutral and charged oxygen vacancies [11,12] and oxygen interstitials [13,14] close to region where the GB is formed in HfO 2 . The leakage currents are related to the structure of the GB which presents favourable percolation paths for electron tunnelling [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental current-voltage characteristics (characters) of n-Si/HfO 2 /Ni PVD structure and simulation (lines) by PATT model at different temperatures(9).…”
mentioning
confidence: 99%
“…The arrows indicate optical transitions during excitation (5.2 eV) and luminescence (Experimental current-voltage characteristics (characters) of n-Si/HfO 2 /Ni ALD structure and simulation (lines) by PATT model at different temperatures(9).…”
mentioning
confidence: 99%